PENGAMALAN ITTIBA' AL-SUNNAH (FOLLOWING THE SUNNAH) DI PONDOK PESANTREN AL-FATAH TEMBORO MAGETAN JAWA TIMUR INDONESIA: Practice of Ittiba’ al-Sunnah (Following the Sunnah) at Al-Fatah Islamic Boarding School Temboro Magetan East Java Indonesia - Syahrizal,; Tengku Kasim, Tengku Sarina Aini (Journal of Islamic Educational Research, 2023)
Love for Allah SWT is beyond words. True love requires allegiance to Him and following His loving Prophet Muhammad SAW. Thus, following the Sunnah shows a servant's commitment to Allah. Ittiba' al-Sunnah must be studied and applied to achieve this. This study examines Indonesia's Sunnah-based Al-Fatah Islamic Boarding School, based on previous research. This qualitative study examines Ittiba' As-Sunnah at Al-Fatah Islamic Boarding School in Temboro, East Java, through in-depth interviews with three important informants. NVivo 4 thematic analysis is used to draw conclusions from interview data. The analysis shows that all informants explain Ittiba As-Sunnah and apply it to Al-Fatah Islamic Boarding School. The survey also found that Al-Fatah Islamic Boarding School promotes Ittiba' As-Sunnah holistically. The hadith curriculum includes Sunnah-based teachings, strategic propagation, the influence of kiai (spiritual leaders), and the boarding school's atmosphere reflect this approach. This research should help Islamic boarding schools and educational institutions establish better plans and programmes. These programmes aim to improve students' practical application of Ittiba As-Sunnah and increase their understanding of kiai and educators' crucial roles in setting examples and guiding students.